“Pengembangan UMKM untuk Meningkatkan Kinerja UMKM di Desa Adat Panglipuran Bali” - Andi Litriyanto; Aditya Joshua K; Aji Sajiwo; Nafa Latifatuzzahro; Maya Putri Amalia; Khalimatus Sa’diyah; Teti Safari (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Panglipuran Traditional Village in Bali has gained international recognition as one of the cleanest tourist villages in the world and serves as a model for culture-based sustainable tourism. The economic foundation of the village relies heavily on the development of Micro, Small, and Medium Enterprises (MSMEs) rooted in local wisdom, which simultaneously function as drivers of economic growth and instruments of cultural preservation. This study seeks to examine the management practices, marketing strategies, and challenges faced by MSMEs in Panglipuran Village. The research applied qualitative methods, including field observation, in-depth interviews with key stakeholders, documentation review, and descriptive analysis. The findings reveal a strong synergy between customary values and economic activities, reflected in flagship products such as bamboo handicrafts, traditional cuisine, and signature beverages. Success factors include an effective organizational structure, the support of customary institutions, and the ability to adopt adaptive marketing approaches. Nonetheless, several challenges were identified, including limited utilization of digital marketing platforms, constraints in production capacity, and insufficient product innovation to meet the demands of broader markets. Recommendations highlight the importance of strengthening online marketing, diversifying product variations, and expanding cooperative networks both within and beyond the village. Overall, the study underscores the significant potential of culture-based MSMEs to enhance community welfare, increase competitiveness, and ensure the sustainability of local traditions within the dynamics of modern tourism.